Assessing ESG and Financial Metrics on Firm Valuation in Non-Cyclical IDX Companies 2020-2024 - Robert, Alexander; Edwin, Edward; Djaja, Kenneth Uli (Business Management Journal, 2025)
Firm value, often proxied by Price-to-Book Value (PBV), reflects market confidence in future performance. In Indonesia’s non-cyclical sector—covering consumer staples, healthcare, and utilities—PBV has experienced volatility between 2020–2024, despite the sector’s traditionally stable nature. This study investigates whether financial indicators such as Return on Assets (ROA), Debt-to-Equity Ratio (DER), and firm size have a stronger impact on PBV than non-financial factors like Environmental, Social, and Governance (ESG) performance. Using purposive sampling, 14 listed firms (70 firm-year observations) were analyzed through panel regression with the Fixed Effect Model (FEM), selected via the Hausman test. The findings indicate that DER has a significant positive effect on PBV, underscoring the importance of capital structure in driving firm valuation. Conversely, ESG score, ROA, and firm size show no significant influence, suggesting that investors in non-cyclical industries continue to prioritize leverage over sustainability or profitability indicators. The study recommends that firms strengthen capital structure management and improve disclosure quality to ensure sustainability efforts are more effectively integrated into valuation. Limitations include a small sample, reliance on secondary ESG data, and a short observation period, suggesting future studies should expand both scope and variables.